Subsurface conditions with geo-hydraulic properties: empirical evidence from Parit Raja, Johor - Musa, Sabariah
Problems in surface runoff management in the study area will eventually involve the subsurface and its layer conditions. The effects highlighted by the media were “pond” flooding and water demand. The study area was covered by peat with an acidic wet top layer. The subsurface was defined by deep layers of compacted clay with low groundwater flow in the ground. A number of surveys and investigation records were found, serving as evidence for these stated problems. To evaluate and define the actual properties of subsurface conditions, this study relates these conditions and property evidence based on in situ and laboratory tests. Geological tests and soil analyses were considered to elaborate on the evidence in the relationship with real site conditions. Portions of the subsurface, limited to a depth of 1.5 m to 30 m, were sampled. Basic geotechnical tests were conducted, and the samples were defined by soil classification, moisture content, and permeability. Onsite tests were conducted to determine the geo-hydraulic parameters on the subsurface interactions according to the onsite physical model of wells. Pumping-and-recovery tests were conducted to determine the subsurface properties related to the storage, transmissivity, drawdown, and flow rate of the aquifer system. All parameters were sandwiched to analyze the subsurface area problem and its geo-hydraulic interactions with storm water management during wet season. With empirical evidence, useful parameters may be able to implement alternative ways to manage surface runoff and local water demand.